Moving beyond the descriptive: The grounded theory of mitigating risk and the theorisation of information literacy. Issue 1 (4th October 2019) - Hicks, Alison
Abstract : Purpose: Information literacy has been consistently undertheorised. The purpose of this paper is to contribute in the ongoing theorisation of information literacy by exploring the meaning and implications of the emergent grounded theory of mitigating risk for information literacy research and practice. Design/methodology/approach: The grounded theory was produced through a qualitative study that was framed by practice theory and the theoretical constructs of cognitive authority and affordance, and employed constructivist grounded theory, semi-structured interviews and photo-elicitation methods to explore the information literacy practices of language-learners overseas. Findings: This paper provides a theoretically rich exploration of language-learner information literacy practices while further identifying the importance of time, affect and information creation within information literacy research and practice as well as the need for the continued theorisation of information literacy concepts. Research limitations/implications: The paper's constructivist grounded theorisation of information literacy remains localised and contextualised rather than generalisable. Practical implications: The paper raises questions and points of reflection that may be used to inform the continued development of information literacy instruction and teaching practices. Originality/value: This paper contributes to an increasingly sophisticated theoretical conceptualisation of information literacy as well as forming a basis for ongoing theoretical development in the field.